8x-3=5x+6                                                                                                                                              7*(3+k)=33+5k

8x-3=5x+6                                                                                                                                              7*(3+k)=33+5k
Гость
Ответ(ы) на вопрос:
Гость
8x-3=5x+6    8х-5х=6+3 3х=9 х=3     7*(3+k)=33+5k 21+7к=33+5к 7к-5к=33-21 2к=12 к=6
Гость
8x-3=5x+6 8х-3-5х-6=0 3х-9=0 3х=9 х=3        7*(3+k)=33+5k 21+7к-33-5к=0 2к=12 к=6    
Не нашли ответ?
Ответить на вопрос
Похожие вопросы